Efektivitas Akun Instagram @Aniesbaswedan Dalam Meningkatkan Kepercayaan Publik - Sri Prihatiningrum; Yopi Kusmiati (Wardah, 2023)
Anies Rasyid Baswedan was the Governor of DKI Jakarta who always shares various information and policies on his personal Instagram account @anesbaswedan. This is because, in this era, Instagram is not only used to express oneself, but also to implement policy transparency and information disclosure with the aim of increasing public trust. One of which is Anies Rasyid Baswedan. Based on this, in this study, researchers looked at the dimensions of the epic model that were most influential in increasing public trust in the @aniesbaswedan Instagram account and saw the effectiveness of the @anesbaswedan Instagram account in increasing public trust based on the EPIC Model. The theory used in this study is the EPIC Model, which is a marketing communication effectiveness measurement tool developed by AC Nielson. This study uses a positivism paradigm with a quantitative approach. The analysis technique used is simple tabulation, the average score is then entered into the EPIC Model scale range. The results of this study indicate that the most influential dimension in this study is the Empathy dimension with a score of 4.26 and the Instagram account @anesbaswedan is declared effective based on an EPIC rate calculation of 4.05 in increasing public trust.